Pengaruh Religius, Kualitas Produk dan Citra Merek Terhadap Pengguna Produk Halal: Studi pada Halal Network Internasional-Herba Penawar Alwahida Indonesia di Kota Bengkulu - Andika Rahman; Yosy Arisandy; Makmur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of religion, product quality and brand image on users of halal products (Study on Halal Network International-Herba Penawar Alwahida Indonesia in Bengkulu City), to test this, researchers used quantitative methods with primary data collection techniques in the form of questionnaires distributed to 58 respondents. The analysis method used in this research is multiple regression analysis method with IBM SPSS 26 application. The results of the study based on partial hypothesis testing (t test) show that religious variables, product quality and brand image partially have a significant effect on halal product users. This can be seen in the results of the religious variable test on halal product users which has a Thitung value of 4,343 > Ttable 2,004 and a significance value of 0.000 < 0.05, the results of the product quality variable test on halal product users which has a Thitung value of 9,235> Ttable 2,004 and a significance value of 0.000 <0.05, while the results of the brand image variable test on halal product users which has a Thitung value of 9,679 > Ttable 2,004 and a significance value of 0.000 < 0.05. The results of the F test religious, product quality, brand image together have a positive and significant effect on halal product users. This can be seen in the Fcount value of 44.306 > Ftable 2.775 and a significant value of 0.000 < 0.05. The test results of the coefficient of determination (R2) obtained Rsquare of 0.711. This shows that the dependent variable of halal product users can be explained by the independent variables of religion, product quality and brand image by 71.1% while 28.9% is explained by other factors outside the variables studied.